Enhancing Human Immunodeficiency Virus-Specific CD8+ T Cell Responses with Heteroclitic Peptides - Adegoke, Adeolu Oyemade; Grant, Michael David (Frontiers in Immunology, 2015)
Human immunodeficiency virus (HIV)-specific CD8+ T cells play a critical role in containing HIV replication and delaying disease progression. However, HIV-specific CD8+ T cells become progressively more “exhausted” as chronic HIV infection proceeds. Symptoms of T cell exhaustion range from expression of inhibitory receptors and selective loss of cytokine production capacity through reduced proliferative potential, impaired differentiation into effector cells and increased susceptibility to apoptosis. While effective combination antiretroviral therapy (cART) durably reduces HIV viremia to undetectable levels, this alone does not restore the full pluripotency of HIV-specific CD8+ T cells. In a number of studies, a subset of peptide epitope variants categorized as heteroclitic, restimulated more potent cellular immune responses in vitro than did the native, immunizing peptides themselves. This property of heteroclitic peptides has been exploited in experimental cancer and chronic viral infection models to promote clearance of transformed cells and persistent viruses. In this review, we consider the possibility that heteroclitic peptides could improve the efficacy of therapeutic vaccines as part of HIV immunotherapy or eradication strategies. We review literature on heteroclitic peptides and illustrate their potential to beneficially modulate the nature of HIV-specific T cell responses towards those found in the small minority of HIV-infected, aviremic cART-naïve persons termed elite controllers (EC) or long term non-progressors (LTNP). Our review suggests the efficacy of HIV vaccines could be improved by identification, testing and incorporation of heteroclitic variants of native HIV peptide epitopes.